The Effects of Substance Abuse and Youth Involvement in Property Crime in Nigeria - Uwais, Idrees Abdullahi; Obumneme, Inyiama Dennis; Sulaiman, Usman Muhammad; Maijama'a, Maryam Sanusi; Gwani, Abdullatif Isa (International Journal of Education, Culture, and Society, 2025)
This study investigates the relationship between substance abuse and youth involvement in property crime in Yelwa area of Bauchi Metropolis, Nigeria. The objectives of this research is to examine the nature of substance abuse among youths, identify the causes leading to their involvement in property crime, assess the effects of substance abuse, explore factors influencing drug use, and provide solutions to combat the problem. The study provides insights in to the socio-economic factors driving substance abuse and its contribution to property crimes such as theft and burglary. The research adopts a quantitative approach, using a survey design. The population consists of 800 youths aged 18 to 35 in Yelwa, and a sample size of 334 was determined using the Taro Yamane formula. Data was collected through self-administered questionnaires, containing both demographic information and targeted questions to assess the relationship between substance abuse and crime. The findings revealed that substance abuse, particularly involving marijuana, alcohol, and inhalants, is prevalent among youths and closely linked to property crimes. The key contributing factors include peer pressure, unemployment, and socio-economic hardship. The study highlights the detrimental impact of substance abuse on both individuals and the community, with increased property crimes and insecurity in Yelwa. The study concludes that comprehensive interventions are needed, including community awareness programs, stronger law enforcement, and youth rehabilitation initiatives. The study recommended that implementation of family-based interventions, youth engagement programs, and greater policy focus on substance abuse prevention at local and national levels.